Redefining the Islamic defenders front's (FPI) identity after its dissolution by the Indonesian government - Maksum, Ali; Jubba, Hasse; Abdullah, Irwan; Wahyuni, Esa Nur; Sopyan, Abdul Rachman (Indonesian Journal of Islam and Muslim Societies, 2023)
This research aims to understand how identity redefinition occurs and whatcultural variables result in identity redefinition. The Indonesian governmenthas disbanded several mass organizations throughout the years. To ensure itssurvival, the group hid among the crowds. Meanwhile, the Islamic DefendersFront (FPI), which the government had disbanded in 2020, was renamed theIslamic United Front, and it maintained a milder stance toward the governmentto survive. Several research studies have examined the government’s rationalefor abolishment. However, research on how organizational actors react to theirorganizations’ dissolution is still scarce. The research examined the former IslamicDefenders Front (FPI) members’ perceptions of their organization’s dissolutionby the government in 2020. The study utilized a qualitative research design. Thedata analysis was performed inductively to ascertain the former FPI members’subjective opinions of the organizational redefinition. The findings indicatedthat former FPI members reinvented their identity after the government’sdisbandment as a means of survival by adopting more lenient, accommodating,and inclusive views toward the government and other mass groups. Also, thedisintegration of radical religious groups may catalyze a new relationship betweenradical Islamic organizations and the state.